Silicon carbide coated silicon-based negative electrode material, silicon carbide negative electrode material, preparation method of silicon carbide negative electrode material, secondary battery and power-related equipment

Through redox reaction and sintering technology, the surface of the silicon-based negative electrode material is uniformly coated with SiC, solving the volume expansion problem of the silicon-based negative electrode material during lithium alloying, and significantly improving its circulation performance and battery life.

CN119725454APending Publication Date: 2025-03-28SI CHUAN HUA YI QING CHUANG XIN CAI LIAO KE JI YOU XIAN GONG SI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411906004.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The sharp volume expansion of silicon-based anode material during lithium alloying leads to material powdering, limiting its application in lithium-ion batteries.

Method used

By mixing the polymer with the silicon source and performing a redox reaction, a precursor is obtained, and a silicon carbide-based negative electrode material is obtained by sintering to achieve uniform coating of SiC on the silicon surface.

Benefits of technology

This method significantly improves the cycling performance of silicon-based negative electrode materials, inhibits the volume expansion of silicon and the side reactions of the electrolyte interface, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725454A_ABST
    Figure CN119725454A_ABST
Patent Text Reader

Abstract

The invention provides a silicon carbide-coated silicon-based negative electrode material, a silicon carbide negative electrode material and a preparation method thereof, a secondary battery and electric equipment, and relates to the field of batteries. The preparation method of the silicon carbide coated silicon-based negative electrode material comprises the following steps: mixing a polymer and a silicon source, and then carrying out an oxidation-reduction reaction to obtain a precursor; and sintering the precursor to obtain the silicon carbide coated silicon-based negative electrode material, the temperature of the oxidation reduction reaction ranges from 1550 DEG C to 3000 DEG C. The preparation method of the silicon carbide negative electrode material comprises the step of carrying out etching treatment on the silicon carbide coated silicon-based negative electrode material by using an etching solution. According to the preparation method of the silicon carbide coated silicon-based negative electrode material provided by the invention, the product obtained through the high-temperature oxidation-reduction reaction is the spheroidized nano silicon, the product is sintered to enable the silicon surface to be uniformly coated with SiC, and finally the nano spherical silicon with the surface uniformly coated with SiC is obtained. The cycle performance of the silicon-based negative electrode with the structure is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a silicon carbide-coated silicon-based negative electrode material, a silicon carbide negative electrode material and a preparation method thereof, a secondary battery and electrical-related equipment. Background Art

[0002] With the rapid development of new energy vehicles and portable electronic products, people have an urgent need for smaller, lighter, more energy-efficient and longer-lasting lithium-ion batteries. Silicon has the advantages of high capacity and low cost, and is considered to be a promising negative electrode material. However, its inherent disadvantages hinder its further application, namely, the rapid volume expansion (>300%) during the lithium alloying process, which leads to material pulverization.

[0003] Therefore, silicon-based negative electrode materials and their derivative materials with excellent electrochemical performance have become a research hotspot. Summary of the invention

[0004] The purpose of the present application is to provide a silicon carbide-coated silicon-based negative electrode material, a silicon carbide negative electrode material and a preparation method thereof, a secondary battery and electrical-related equipment to solve the above-mentioned problems.

[0005] To achieve the above objectives, this application adopts the following technical solutions:

[0006] A method for preparing a silicon carbide-coated silicon-based negative electrode material, comprising:

[0007] The polymer and the silicon source are mixed and then subjected to a redox reaction to obtain a precursor;

[0008] Sintering the precursor to obtain the silicon carbide-coated silicon-based negative electrode material;

[0009] The temperature of the redox reaction is 1550-3000°C.

[0010] Preferably, the polymer includes an M polymer, and the M polymer includes at least one of polyvinyl chloride, polytetrafluoroethylene, and polyvinylidene fluoride;

[0011] Preferably, the polymer further comprises N polymers, and satisfies one or more of the following conditions:

[0012] (1) The N polymer includes at least one of polyamide, polyacrylic acid, ethylene-vinyl acetate copolymer, polyethylene terephthalate, polybutylene terephthalate, polystyrene, and polycarbonate;

[0013] (2) The mass ratio of the M polymer to the N polymer is (0.01-30.5):1;

[0014] (3) The particle sizes of the M polymer and the N polymer are independently 0.05-500 μm.

[0015] Furthermore, the method for preparing the silicon carbide-coated silicon-based negative electrode material satisfies one or more of the following conditions:

[0016] A. The silicon source includes silicon powder;

[0017] B. The particle size of the silicon source is 0.01-400 μm;

[0018] C. The mass ratio of the silicon source to the polymer is (0.01-100): 1;

[0019] D. The mixing includes one or more of ultrasound, mechanical stirring, and vibration ball milling;

[0020] E. The mixing time is 0.1-36h;

[0021] F. The mixed solvent includes one or more of ethanol, pure water, isopropanol, ether, methyl acetate, and acetone;

[0022] G. The atmosphere of the redox reaction includes one or more of nitrogen, air, argon, carbon dioxide, and oxygen;

[0023] H. The temperature of the redox reaction is 2000-3000°C, and the reaction time is 0.01-60min;

[0024] I. The sintering atmosphere is a mixture of oxygen and nitrogen, a mixture of oxygen and argon, or a mixture of oxygen and carbon dioxide, wherein the volume content of oxygen is not less than 1%;

[0025] J. The sintering temperature is 300-2000°C and the insulation time is 1-12h.

[0026] The present application also provides a silicon carbide coated silicon-based negative electrode material, which is prepared using the method for preparing the silicon carbide coated silicon-based negative electrode material.

[0027] Preferably, the silicon carbide-coated silicon-based negative electrode material meets one or more of the following conditions:

[0028] A. The particle size of the silicon carbide coated silicon-based negative electrode material is 0.01-500 μm;

[0029] B. The silicon carbide coated silicon-based negative electrode material comprises a core and a shell coating the core, the particle size of the core is greater than or equal to 0.01 μm and less than 500 μm, and the thickness of the shell is 0.0001-100 μm.

[0030] The present application also provides a method for preparing a silicon carbide negative electrode material, comprising:

[0031] The silicon carbide coated silicon-based negative electrode material is etched with an etching solution.

[0032] Preferably, the etching solution includes one or more of potassium hydroxide, sodium hydroxide, tetramethylammonium hydroxide, hydrochloric acid, hydrofluoric acid, and ethylenediaminocatechol;

[0033] Preferably, the concentration of the etching solution is 0.1-5 mol / L.

[0034] The present application also provides a silicon carbide negative electrode material, which is prepared by the preparation method of the silicon carbide negative electrode material.

[0035] The present application also provides a secondary battery, the raw materials of which include the silicon carbide-coated silicon-based negative electrode material and / or the silicon carbide negative electrode material.

[0036] The present application also provides an electrical device, including the secondary battery.

[0037] Compared with the prior art, the beneficial effects of this application include:

[0038] The present application provides a method for preparing a silicon carbide-coated silicon-based negative electrode material. The product obtained by a high-temperature redox reaction is spherical nano-silicon. Sintering the product allows the silicon surface to be uniformly coated with SiC, and finally nano-spherical silicon with a surface uniformly coated with SiC is obtained. The silicon-based negative electrode with this structure has greatly improved its cycle performance.

[0039] The silicon carbide-coated silicon-based negative electrode material provided in the present application, β-SiC, has excellent structural stability, low conversion potential, and high capacity. Uniformly coating SiC on the surface of nano-silicon can well inhibit the volume expansion of silicon and can inhibit the interface side reactions between silicon and electrolyte.

[0040] The method for preparing the silicon carbide negative electrode material provided in the present application obtains nano-sized β-SiC through a low-cost and easily industrializable etching method on the basis of obtaining a silicon carbide-coated silicon-based negative electrode material.

[0041] The silicon carbide negative electrode material provided in the present application has the characteristics of high specific capacity and long cycle life.

[0042] The secondary battery and electrical equipment provided by the present application have excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0044] Figure 1 The transmission electron microscope test results of the silicon carbide-coated silicon-based negative electrode material obtained in Example 1;

[0045] Figure 2 The XRD test results of the silicon carbide-coated silicon-based negative electrode material obtained in Example 1;

[0046] Figure 3 The 100-cycle cycle curve of the battery prepared by the silicon carbide-coated silicon-based negative electrode material obtained in Example 1;

[0047] Figure 4 This is the scanning electron microscope test result of the silicon carbide negative electrode material obtained in Example 13;

[0048] Figure 5 The transmission electron microscope test results of the silicon carbide negative electrode material obtained in Example 13;

[0049] Figure 6 This is the XRD test result of the silicon carbide negative electrode material obtained in Example 13;

[0050] Figure 7 This is the 100-cycle cycle curve of the battery prepared using the silicon carbide negative electrode material obtained in Example 13. DETAILED DESCRIPTION

[0051] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:

[0052] A method for preparing a silicon carbide-coated silicon-based negative electrode material, comprising:

[0053] The polymer and the silicon source are mixed and then subjected to a redox reaction to obtain a precursor;

[0054] Sintering the precursor to obtain the silicon carbide-coated silicon-based negative electrode material;

[0055] The temperature of the redox reaction is 1550-3000°C.

[0056] Optionally, the temperature of the redox reaction can be 1550°C, 1600°C, 1700°C, 1800°C, 1900°C, 2000°C, 2100°C, 2200°C, 2300°C, 2400°C, 2500°C, 2600°C, 2700°C, 2800°C, 2900°C, 3000°C or any value between 1550-3000°C.

[0057] In an optional embodiment, the polymer includes an M polymer, and the M polymer includes at least one of polyvinyl chloride, polytetrafluoroethylene, and polyvinylidene fluoride;

[0058] In an optional embodiment, the polymer further comprises N polymers, and satisfies one or more of the following conditions:

[0059] (1) The N polymer includes at least one of polyamide, polyacrylic acid, ethylene-vinyl acetate copolymer, polyethylene terephthalate, polybutylene terephthalate, polystyrene, and polycarbonate;

[0060] The main purpose of adding N polymer is to promote the activity of M polymer, so that the activity of subsequent redox reactions is increased. At the same time, through the coordination of N polymer and M polymer, the integrity and stability of the product coating layer are improved, thereby improving the electrochemical properties of the material.

[0061] (2) The mass ratio of the M polymer to the N polymer is (0.01-30.5):1;

[0062] Optionally, the mass ratio of the M polymer to the N polymer may be 0.01:1, 0.05:1, 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 30.5:1 or any value between (0.01-30.5):1;

[0063] (3) The particle sizes of the M polymer and the N polymer are independently 0.05-500 μm.

[0064] Optionally, the particle sizes of the M polymer and the N polymer may independently be 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 10 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm or any value between 0.05-500 μm.

[0065] In an optional embodiment, the method for preparing the silicon carbide-coated silicon-based negative electrode material satisfies one or more of the following conditions:

[0066] A. The silicon source includes silicon powder;

[0067] B. The particle size of the silicon source is 0.01-400 μm;

[0068] Optionally, the particle size of the silicon source may be 0.01 μm, 0.1 μm, 0.5 μm, 1 μm, 10 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm or any value between 0.01-400 μm;

[0069] C. The mass ratio of the silicon source to the polymer is (0.01-100): 1;

[0070] Optionally, the mass ratio of the silicon source to the polymer can be 0.01:1, 0.05:1, 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1, 60:1, 65:1, 70:1, 75:1, 80:1, 85:1, 90:1, 95:1, 100:1 or any value between (0.01-100):1;

[0071] D. The mixing includes one or more of ultrasound, mechanical stirring, and vibration ball milling;

[0072] E. The mixing time is 0.1-36h;

[0073] Optionally, the mixing time can be 0.1h, 0.5h, 1h, 6h, 10h, 12h, 18h, 24h, 30h, 36h or any value between 0.1-36h;

[0074] F. The mixed solvent includes one or more of ethanol, pure water, isopropanol, ether, methyl acetate, and acetone;

[0075] G. The present application does not particularly limit the atmosphere of the redox reaction. As some preferred embodiments, the atmosphere of the redox reaction includes one or more of nitrogen, air, argon, carbon dioxide, and oxygen;

[0076] H. The temperature of the redox reaction is 2000-3000°C, and the reaction time is 0.01-60min;

[0077] Optionally, the temperature of the redox reaction can be 2000°C, 2100°C, 2200°C, 2300°C, 2400°C, 2500°C, 2600°C, 2700°C, 2800°C, 2900°C, 3000°C or any value between 2000-3000°C; the reaction time can be 0.01min, 0.1min, 0.5min, 1min, 5min, 10min, 30min, 60min or any value between 0.01-60min;

[0078] I. The sintering atmosphere is a mixture of oxygen and nitrogen, a mixture of oxygen and argon, or a mixture of oxygen and carbon dioxide, wherein the volume content of oxygen is not less than 1%;

[0079] J. The sintering temperature is 300-2000°C and the insulation time is 1-12h.

[0080] Optionally, the sintering temperature can be 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, 1900°C, 2000°C or any value between 300-2000°C, and the holding time can be 1h, 2h, 4h, 6h, 8h, 10h, 12h or any value between 1-12h.

[0081] The present application also provides a silicon carbide coated silicon-based negative electrode material, which is prepared using the method for preparing the silicon carbide coated silicon-based negative electrode material.

[0082] In an optional embodiment, the silicon carbide-coated silicon-based negative electrode material satisfies one or more of the following conditions:

[0083] A. The particle size of the silicon carbide coated silicon-based negative electrode material is 0.01-500 μm;

[0084] Optionally, the particle size of the silicon carbide-coated silicon-based negative electrode material may be 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm or any value between 0.01-500 μm;

[0085] B. The silicon carbide coated silicon-based negative electrode material comprises a core and a shell coating the core, the particle size of the core is greater than or equal to 0.01 μm and less than 500 μm, and the thickness of the shell is 0.0001-100 μm.

[0086] Optionally, the particle size of the inner core can be 0.01μm, 0.05μm, 0.1μm, 0.5μm, 1μm, 5μm, 10μm, 50μm, 100μm, 200μm, 300μm, 400μm, 450μm, 499μm or any value greater than or equal to 0.01μm and less than 500μm, and the thickness of the outer shell can be 0.0001μm, 0.0005μm, 0.001μm, 0.005μm, 0.01μm, 0.05μm, 0.1μm, 0.5μm, 1μm, 5μm, 10μm, 50μm, 100μm or any value between 0.0001-100μm.

[0087] The present application also provides a method for preparing a silicon carbide negative electrode material, comprising:

[0088] The silicon carbide coated silicon-based negative electrode material is etched with an etching solution.

[0089] In an optional embodiment, the etching solution includes one or more of potassium hydroxide, sodium hydroxide, tetramethylammonium hydroxide, hydrochloric acid, hydrofluoric acid, and ethylenediaminocatechol;

[0090] In an optional embodiment, the concentration of the etching solution is 0.1-5 mol / L.

[0091] Optionally, the concentration of the etching solution may be 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L or any value between 0.1-5 mol / L.

[0092] The present application also provides a silicon carbide negative electrode material, which is prepared by the preparation method of the silicon carbide negative electrode material.

[0093] The present application also provides a secondary battery, the raw materials of which include the silicon carbide-coated silicon-based negative electrode material and / or the silicon carbide negative electrode material.

[0094] The secondary battery can be a common secondary battery such as a potassium ion battery, a lithium ion battery, or a sodium ion battery.

[0095] The present application also provides an electrical device, including the secondary battery.

[0096] The electrical equipment referred to in this application may be, for example, electric vehicles, electric bicycles, electronic watches, power banks, energy storage station energy storage equipment, and other equipment that directly uses the secondary battery of this application for power supply or energy storage, or indirectly uses (externally connects) the secondary battery provided by this application for power supply or energy storage.

[0097] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0098] 1. Preparation of silicon carbide coated silicon-based negative electrode materials

[0099] Example 1

[0100] This embodiment provides a silicon carbide-coated silicon-based negative electrode material, and the preparation method thereof comprises the following steps:

[0101] Polyacrylic acid, polyvinyl chloride, and ethylene-vinyl acetate copolymer (all with a particle size of 10 μm) were uniformly mixed in a mass ratio of 35:64:1 to obtain a mixture A. Silicon powder (particle size of 8 μm) and mixture A were placed in ethanol in a mass ratio of 1:1 and mechanically stirred for 1 hour. After centrifugation and drying, product B was obtained. Then product B was placed in a reactor in a nitrogen atmosphere and subjected to a redox reaction at a high temperature of 2000°C for 1 minute to obtain product C. Product C was sintered at 700°C in an oxygen-nitrogen mixed atmosphere with an oxygen content of 80% and kept warm for 3 hours. A nano-spherical silicon-based negative electrode material with a surface uniformly coated with SiC was obtained.

[0102] The particle size of the silicon-based negative electrode material is 0.023 μm; the particle size of the inner core is 0.02 μm, and the thickness of the outer shell is 0.0015 μm.

[0103] Figure 1 The transmission electron microscope test results of the silicon carbide-coated silicon-based negative electrode material obtained in Example 1;

[0104] Figure 2 This is the XRD test result of the silicon carbide-coated silicon-based negative electrode material obtained in Example 1.

[0105] Example 2

[0106] This embodiment provides a silicon carbide-coated silicon-based negative electrode material, and the preparation method thereof comprises the following steps:

[0107] Polybutylene terephthalate, polytetrafluoroethylene, and polyamide (all with a particle size of 0.3 μm) were uniformly mixed in a mass ratio of 30:1:69 to obtain a mixture A. Silicon powder (particle size of 0.04 μm) and mixture A were placed in ether for ultrasonic treatment for 4 hours in a mass ratio of 4:1. After centrifugation and drying, product B was obtained. Product B was then placed in a reactor in an air atmosphere and subjected to a redox reaction at a high temperature of 3000°C for 0.1 min to obtain product C. Product C was sintered at 450°C in an oxygen-argon mixed atmosphere with an oxygen content of 1% and kept warm for 6 hours. A nano-spherical silicon-based negative electrode material with a surface uniformly coated with SiC was obtained.

[0108] The particle size of the silicon-based negative electrode material is 0.08 μm; the particle size of the inner core is 0.075 μm, and the thickness of the outer shell is 0.0025 μm.

[0109] Example 3

[0110] This embodiment provides a silicon carbide-coated silicon-based negative electrode material, and the preparation method thereof comprises the following steps:

[0111] Polystyrene, polycarbonate, and polyethylene terephthalate (all with a particle size of 0.2 μm) were uniformly mixed at a mass ratio of 1:70:29 to obtain a mixture A, and silicon powder (particle size of 10 μm) and mixture A were vibrated and ball-milled for 1 hour at a mass ratio of 0.02:1 to obtain product B. Then product B was placed in a reactor in an argon atmosphere, and a redox reaction was carried out at a high temperature of 2500°C for 2 minutes to obtain product C. Product C was sintered at 350°C in an atmosphere of oxygen mixed with carbon dioxide with an oxygen content of 20%, and kept warm for 1 hour. A nano-spherical silicon-based negative electrode material with a surface uniformly coated with SiC was obtained.

[0112] The particle size of the silicon-based negative electrode material is 0.1 μm; the particle size of the inner core is 0.08 μm, and the thickness of the outer shell is 0.01 μm.

[0113] Example 4

[0114] This embodiment provides a silicon carbide-coated silicon-based negative electrode material, and the preparation method thereof comprises the following steps:

[0115] Polyvinyl chloride, polyvinylidene fluoride, and polystyrene (all with a particle size of 7 μm) were uniformly mixed in a mass ratio of 24:11:65 to obtain a mixture A. Silicon powder (particle size of 0.04 μm) and mixture A were placed in acetone at a mass ratio of 5:1 for ultrasonication for 12 hours, and product B was obtained after centrifugation and drying. Then product B was placed in a reactor in a carbon dioxide atmosphere, and a redox reaction was carried out at a high temperature of 2300°C for 5 minutes to obtain product C. Product C was sintered at 1500°C in a 100% oxygen atmosphere and kept warm for 12 hours. A nano-spherical silicon-based negative electrode material with SiC uniformly coated on the surface was obtained.

[0116] The particle size of the silicon-based negative electrode material is 0.15 μm; the particle size of the inner core is 0.1 μm, and the thickness of the outer shell is 0.025 μm.

[0117] Example 5

[0118] This embodiment provides a silicon carbide-coated silicon-based negative electrode material, and the preparation method thereof comprises the following steps:

[0119] Polybutylene terephthalate, polytetrafluoroethylene, and polyacrylic acid (all with a particle size of 0.5 μm) were uniformly mixed in a mass ratio of 42:3:55 to obtain a mixture A. Silicon powder (particle size of 10 μm) and mixture A were placed in pure water at a mass ratio of 59:1 and mechanically stirred for 8 hours. After centrifugation and drying, product B was obtained. Then product B was placed in a reactor in an oxygen atmosphere and subjected to a redox reaction at a high temperature of 2100°C for 2 minutes to obtain product C. Product C was sintered at 1000°C in an oxygen-argon mixed atmosphere with an oxygen content of 50% and kept warm for 10 hours. A nano-spherical silicon-based negative electrode material with a surface uniformly coated with SiC was obtained.

[0120] The particle size of the silicon-based negative electrode material is 0.07 μm; the particle size of the inner core is 0.06 μm, and the thickness of the outer shell is 0.005 μm.

[0121] Example 6

[0122] This embodiment provides a silicon carbide-coated silicon-based negative electrode material, and the preparation method thereof comprises the following steps:

[0123] Polyvinylidene fluoride and polybutylene terephthalate (particle size of 80 μm) were uniformly mixed at a mass ratio of 9:1 to obtain mixture A. Silicon powder (particle size of 10 μm) and mixture A were placed in ether at a mass ratio of 0.5:1 and mechanically stirred for 3 hours. After centrifugation and drying, product B was obtained. Then product B was placed in a reactor in a nitrogen atmosphere and subjected to a redox reaction at a high temperature of 2330°C for 8 minutes to obtain product C. Product C was sintered at 300°C in an oxygen-nitrogen mixed atmosphere with an oxygen content of 10% and kept warm for 1 hour. A nano-spherical silicon-based negative electrode material with SiC uniformly coated on the surface was obtained.

[0124] The particle size of the silicon-based negative electrode material is 0.01 μm; the particle size of the inner core is 0.0095 μm, and the thickness of the outer shell is 0.00025 μm.

[0125] Example 7

[0126] This embodiment provides a silicon carbide-coated silicon-based negative electrode material, and the preparation method thereof comprises the following steps:

[0127] Polyvinyl chloride and polytetrafluoroethylene (particle size of 11 μm) were uniformly mixed in a mass ratio of 10:1 to obtain mixture A, and silicon powder (particle size of 0.05 μm) and mixture A were vibrated and ball-milled in a mass ratio of 1:1 for 9 hours to obtain product B. Then product B was placed in a reactor in a carbon dioxide atmosphere, and a redox reaction was carried out at a high temperature of 2500°C for 0.5 minutes to obtain product C. Product C was sintered at 400°C in an oxygen-carbon dioxide atmosphere with an oxygen content of 33%, and kept warm for 7 hours. A nano-spherical silicon-based negative electrode material with SiC uniformly coated on the surface was obtained.

[0128] The particle size of the silicon-based negative electrode material is 0.03 μm; the particle size of the inner core is 0.02 μm, and the thickness of the outer shell is 0.005 μm.

[0129] Example 8

[0130] This embodiment provides a silicon carbide-coated silicon-based negative electrode material, and the preparation method thereof comprises the following steps:

[0131] Polyethylene terephthalate and polycarbonate (both with a particle size of 100 μm) were uniformly mixed at a mass ratio of 33:1 to obtain a mixture A. Silicon powder (particle size of 0.9 μm) and mixture A were placed in isopropyl acetone at a mass ratio of 13:1 and mechanically stirred for 0.1 h. After centrifugation and drying, product B was obtained. Product B was then placed in a reactor in an air atmosphere and subjected to a redox reaction at a high temperature of 3000°C for 1 min to obtain product C. Product C was sintered at 800°C in an oxygen-nitrogen mixed atmosphere with an oxygen content of 25% and kept warm for 10 h. A nano-spherical silicon-based negative electrode material with a surface uniformly coated with SiC was obtained.

[0132] The particle size of the silicon-based negative electrode material is 0.02 μm; the particle size of the inner core is 0.019 μm, and the thickness of the outer shell is 0.0005 μm.

[0133] Example 9

[0134] This embodiment provides a silicon carbide-coated silicon-based negative electrode material, and the preparation method thereof comprises the following steps:

[0135] Polyamide and polyacrylic acid (particle size of both is 15 μm) are uniformly mixed at a mass ratio of 0.67:1 to obtain mixture A. Silicon powder (particle size of 15 μm) and mixture A are placed in ethanol at a mass ratio of 5:1 for ultrasonication for 5 hours, and product B is obtained after centrifugation and drying. Product B is then placed in a reactor in an argon atmosphere, and a redox reaction is carried out at a high temperature of 2000°C for 0.2 minutes to obtain product C. Product C is sintered at 660°C in an oxygen-mixed carbon dioxide atmosphere with an oxygen content of 45%, and kept warm for 6 hours. A nano-spherical silicon-based negative electrode material with SiC uniformly coated on the surface is obtained.

[0136] The particle size of the silicon-based negative electrode material is 0.7 μm; the particle size of the inner core is 0.4 μm, and the thickness of the outer shell is 0.15 μm.

[0137] Example 10

[0138] This embodiment provides a silicon carbide-coated silicon-based negative electrode material, and the preparation method thereof comprises the following steps:

[0139] Polyethylene terephthalate and polyvinylidene fluoride (particle size of 18 μm) were uniformly mixed in a mass ratio of 1:1 to obtain mixture A. Silicon powder (particle size of 22 μm) and mixture A were placed in methyl acetate in a mass ratio of 50:1 and mechanically stirred for 2 hours. After centrifugation and drying, product B was obtained. Then product B was placed in a reactor in an air atmosphere and subjected to a redox reaction at a high temperature of 2800°C for 3 minutes to obtain product C. Product C was sintered at 600°C in an oxygen-mixed carbon dioxide atmosphere with an oxygen content of 5% and kept warm for 4 hours. A nano-spherical silicon-based negative electrode material with SiC uniformly coated on the surface was obtained.

[0140] The particle size of the silicon-based negative electrode material is 0.09 μm; the particle size of the inner core is 0.085 μm, and the thickness of the outer shell is 0.0025 μm.

[0141] Embodiment 11

[0142] This embodiment provides a silicon carbide-coated silicon-based negative electrode material, and the preparation method thereof comprises the following steps:

[0143] Polyvinylidene fluoride (particle size 8μm) was used as mixture A, and silicon powder (particle size 22μm) and mixture A were placed in methyl acetate in a mass ratio of 1:1 for ultrasonic treatment for 2h, and product B was obtained after centrifugation and drying. Then product B was placed in a reactor in a nitrogen atmosphere, and a redox reaction was carried out at a high temperature of 2600℃ for 0.5min to obtain product C. Product C was sintered at 680℃ in an oxygen-carbon dioxide atmosphere with an oxygen content of 20%, and kept warm for 7h. A nano-spherical silicon-based negative electrode material with SiC uniformly coated on the surface was obtained.

[0144] The particle size of the silicon-based negative electrode material is 0.6 μm; the particle size of the inner core is 0.48 μm, and the thickness of the outer shell is 0.06 μm.

[0145] Example 12

[0146] This embodiment provides a silicon carbide-coated silicon-based negative electrode material, and the preparation method thereof comprises the following steps:

[0147] Polytetrafluoroethylene (particle size of 0.9 μm) was used as mixture A, and silicon powder (particle size of 0.05 μm) and mixture A were placed in pure water at a mass ratio of 3:1 for ultrasonic treatment for 5 hours, and product B was obtained after centrifugation and drying. Then product B was placed in a reactor in an air atmosphere, and a redox reaction was carried out at a high temperature of 2000°C for 0.2 minutes to obtain product C. Product C was sintered at 800°C in an oxygen-nitrogen mixed atmosphere with an oxygen content of 10%, and kept warm for 4 hours. A nano-spherical silicon-based negative electrode material with SiC uniformly coated on the surface was obtained.

[0148] The particle size of the silicon-based negative electrode material is 0.76 μm; the particle size of the inner core is 0.69 μm, and the thickness of the outer shell is 0.035 μm.

[0149] Comparative Example 1

[0150] The difference from Example 1 is that the mixture A is ethylene-vinyl acetate copolymer and the redox reaction temperature is 700°C. 2 Nanosheet silicon-based negative electrode materials.

[0151] Comparative Example 2

[0152] The difference from Example 1 is that corn starch is used instead of polymer, and the temperature of the redox reaction is 450°C. Finally, the surface-coated SiO 2 Micron-flaky silicon-based negative electrode material.

[0153] Electrochemical performance test

[0154] The silicon-based negative electrode material prepared in the above Examples 1-12 and Comparative Examples 1-2 was used as the active material, copper foil was used as the current collector, the active material, Super P Li, and the binder were made into negative electrode sheets in a mass ratio of 8:1:1, and metallic lithium was used as the counter electrode to assemble a button-type half-cell.

[0155] The electrochemical performance test results are shown in Table 1.

[0156] Table 1 Electrochemical performance test results 1

[0157]

[0158] In Comparative Examples 1 and 2, since the carbon source does not contain halogen-substituted vinyl polymers, the redox reaction temperature is low, the product is not SiC-coated, and the silicon is not nano-spherical, resulting in reduced specific capacity and coulombic efficiency.

[0159] Figure 3 This is a 100-cycle cycle curve of a battery prepared using the silicon carbide-coated silicon-based negative electrode material obtained in Example 1.

[0160] 2. Preparation of β-silicon carbide negative electrode materials

[0161] Example 13

[0162] This embodiment provides a β-silicon carbide negative electrode material, and the preparation method thereof is as follows:

[0163] Polyacrylic acid, polyvinyl chloride, and polyamide (all with a particle size of 10 μm) were uniformly mixed in a mass ratio of 11:12:1 to obtain a mixture A, and silicon powder (particle size of 10 μm) and mixture A were vibrated and ball-milled for 3 hours in a mass ratio of 7:1 to obtain product B. Then product B was placed in a reactor in an air atmosphere and subjected to a redox reaction at a high temperature of 2100°C for 1 minute to obtain product C. Product C was sintered at 500°C in an oxygen-nitrogen mixed atmosphere with an oxygen content of 20%, and kept warm for 6 hours to obtain product D. Product D was reacted with a 4 mol / L potassium hydroxide solution to obtain a nano-β-SiC negative electrode material.

[0164] Figure 4 This is the scanning electron microscope test result of the silicon carbide negative electrode material obtained in Example 13; Figure 5 The transmission electron microscope test results of the silicon carbide negative electrode material obtained in Example 13; Figure 6 This is the XRD test result of the silicon carbide negative electrode material obtained in Example 13.

[0165] Embodiment 14

[0166] This embodiment provides a β-silicon carbide negative electrode material, and the preparation method thereof is as follows:

[0167] Polyacrylic acid, polytetrafluoroethylene, and polystyrene (all with a particle size of 0.9 μm) were uniformly mixed in a mass ratio of 21:1:2 to obtain a mixture A. Silicon powder (particle size of 0.05 μm) and mixture A were placed in ether in a mass ratio of 1:1 and mechanically stirred for 4 hours. After centrifugation and drying, product B was obtained. Then product B was placed in a reactor in an argon atmosphere and subjected to a redox reaction at a high temperature of 3000°C for 0.3 minutes to obtain product C. Product C was sintered at 400°C in an oxygen-argon mixed atmosphere with an oxygen content of 80%, and kept warm for 3 hours to obtain product D. Product D was reacted with a 0.5 mol / L sodium hydroxide solution to obtain a nano-β-SiC negative electrode material.

[0168] Embodiment 15

[0169] Polyacrylic acid, polyethylene terephthalate, and polystyrene (all with a particle size of 23 μm) were uniformly mixed in a mass ratio of 11:3:1 to obtain a mixture A. Silicon powder (particle size of 110 μm) and mixture A were placed in isopropanol in a mass ratio of 1:1 for ultrasonic treatment for 4 hours, and product B was obtained after centrifugation and drying. Product B was then placed in a reactor in a carbon dioxide atmosphere, and a redox reaction was carried out at a high temperature of 2100°C for 5 minutes to obtain product C. Product C was sintered at 550°C in a 50% oxygen atmosphere and kept warm for 2 hours to obtain product D. Product D was reacted with a 3 mol / L hydrochloric acid solution to obtain a nano-β-SiC negative electrode material.

[0170] Example 16

[0171] This embodiment provides a β-silicon carbide negative electrode material, and the preparation method thereof is as follows:

[0172] Polyvinylidene fluoride, polyethylene terephthalate, and polycarbonate (particle size of 0.05 μm) were uniformly mixed in a mass ratio of 22:11:1 to obtain a mixture A. Silicon powder (particle size of 0.2 μm) and mixture A were placed in isopropanol in a mass ratio of 1:1 and mechanically stirred for 4 hours. After centrifugation and drying, product B was obtained. Then product B was placed in a reactor in a carbon dioxide atmosphere and subjected to a redox reaction at a high temperature of 2400°C for 8 minutes to obtain product C. Product C was sintered at 550°C in an oxygen-mixed carbon dioxide atmosphere with an oxygen content of 30%, and kept warm for 2 hours to obtain product D. Product D was reacted with a 3 mol / L hydrofluoric acid solution to obtain a nano-β-SiC negative electrode material.

[0173] Embodiment 17

[0174] This embodiment provides a β-silicon carbide negative electrode material, and the preparation method thereof is as follows:

[0175] Polyvinyl chloride, polyethylene terephthalate, and polycarbonate (all with a particle size of 11 μm) were uniformly mixed in a mass ratio of 1:34:1 to obtain a mixture A, and silicon powder (particle size of 30 μm) and mixture A were vibrated and ball-milled for 3 hours in a mass ratio of 1:1 to obtain product B. Then product B was placed in a reactor in an oxygen atmosphere, and a redox reaction was carried out at a high temperature of 2400°C for 0.5 minutes to obtain product C. Product C was sintered at 450°C in an oxygen-mixed carbon dioxide atmosphere with an oxygen content of 50%, and kept warm for 6 hours to obtain product D. Product D was reacted with a 2 mol / L tetramethylammonium hydroxide solution to obtain a nano-β-SiC negative electrode material.

[0176] Embodiment 18

[0177] This embodiment provides a β-silicon carbide negative electrode material, and the preparation method thereof is as follows:

[0178] Polyvinyl chloride and polyethylene-vinyl acetate copolymer (particle size of 34 μm) were uniformly mixed in a mass ratio of 1:1 to obtain mixture A, and silicon powder (particle size of 10 μm) and mixture A were vibrated and ball-milled for 2 hours in a mass ratio of 1:2 to obtain product B. Then product B was placed in a reactor in an argon atmosphere and subjected to a redox reaction at a high temperature of 2000°C for 10 minutes to obtain product C. Product C was sintered at 400°C in an oxygen-argon mixed atmosphere with an oxygen content of 20%, and kept warm for 6 hours to obtain product D. Product D was reacted with a 2 mol / L ethylenediamine catechol solution to obtain a nano-β-SiC negative electrode material.

[0179] Embodiment 19

[0180] This embodiment provides a β-silicon carbide negative electrode material, and the preparation method thereof is as follows:

[0181] Polytetrafluoroethylene and polyethylene-vinyl acetate copolymer (particle size of 80 μm) were uniformly mixed at a mass ratio of 1:20 to obtain mixture A. Silicon powder (particle size of 0.08 μm) and mixture A were placed in acetone at a mass ratio of 1:1 and mechanically stirred for 5 hours. After centrifugation and drying, product B was obtained. Then product B was placed in a reactor in an argon atmosphere and subjected to a redox reaction at a high temperature of 2700°C for 2 minutes to obtain product C. Product C was sintered at 700°C in an oxygen-nitrogen mixed atmosphere with an oxygen content of 80%, and kept warm for 4 hours to obtain product D. Product D was reacted with a 2 mol / L potassium hydroxide solution to obtain a nano-β-SiC negative electrode material.

[0182] Embodiment 20

[0183] This embodiment provides a β-silicon carbide negative electrode material, and the preparation method thereof is as follows:

[0184] Polyamide and polyacrylic acid (particle size of 7 μm) were uniformly mixed in a mass ratio of 1:9 to obtain mixture A. Silicon powder (particle size of 0.1 μm) and mixture A were placed in ethanol in a mass ratio of 1:1 for ultrasonic treatment for 5 hours, and product B was obtained after centrifugation and drying. Product B was then placed in a reactor in a nitrogen atmosphere and subjected to a redox reaction at 2900°C for 1 minute to obtain product C. Product C was sintered at 700°C in an oxygen-nitrogen mixed atmosphere with an oxygen content of 33%, and kept warm for 4 hours to obtain product D. Product D was reacted with a 2 mol / L hydrochloric acid solution to obtain a nano-β-SiC negative electrode material.

[0185] Embodiment 21

[0186] This embodiment provides a β-silicon carbide negative electrode material, and the preparation method thereof is as follows:

[0187] Polyamide and polyacrylic acid (particle size of 70 μm) were uniformly mixed in a mass ratio of 1:4 to obtain mixture A, and silicon powder (particle size of 21 μm) and mixture A were vibrated and ball-milled for 4 hours in a mass ratio of 1:1 to obtain product B. Then product B was placed in a reactor in an air atmosphere and subjected to a redox reaction at a high temperature of 2300°C for 7 minutes to obtain product C. Product C was sintered at 500°C in an oxygen-argon mixed atmosphere with an oxygen content of 45%, and kept warm for 4 hours to obtain product D. Product D was reacted with a 1 mol / L hydrofluoric acid solution to obtain a nano-β-SiC negative electrode material.

[0188] Embodiment 22

[0189] This embodiment provides a β-silicon carbide negative electrode material, and the preparation method thereof is as follows:

[0190] Polystyrene and polycarbonate (particle size of 20 μm) were uniformly mixed in a mass ratio of 1:1 to obtain mixture A. Silicon powder (particle size of 1 μm) and mixture A were placed in methyl acetate in a mass ratio of 2:1 for ultrasonic treatment for 2 hours, and product B was obtained after centrifugation and drying. Product B was then placed in a reactor in a carbon dioxide atmosphere and subjected to a redox reaction at a high temperature of 2000°C for 14 minutes to obtain product C. Product C was sintered at 500°C in an oxygen-argon mixed atmosphere with an oxygen content of 25%, and kept warm for 5 hours to obtain product D. Product D was reacted with a 1 mol / L sodium hydroxide solution to obtain a nano-β-SiC negative electrode material.

[0191] Embodiment 23

[0192] This embodiment provides a β-silicon carbide negative electrode material, and the preparation method thereof is as follows:

[0193] Polyvinyl chloride (particle size of 2 μm) was used as mixture A, and silicon powder (particle size of 3 μm) and mixture A were placed in ethanol at a mass ratio of 1:1 for ultrasonic treatment for 0.8 h, and product B was obtained after centrifugation and drying. Then product B was placed in a reactor in an air atmosphere, and a redox reaction was carried out at a high temperature of 2400°C for 1 min to obtain product C. Product C was sintered at 900°C in an oxygen-nitrogen mixed atmosphere with an oxygen content of 25%, and kept warm for 3 hours to obtain product D. Product D was reacted with 1.2 mol / L sodium hydroxide solution to obtain nano β-SiC negative electrode material.

[0194] Embodiment 24

[0195] This embodiment provides a β-silicon carbide negative electrode material, and the preparation method thereof is as follows:

[0196] Polyvinylidene fluoride (particle size of 0.2μm) was used as mixture A, and silicon powder (particle size of 0.85μm) and mixture A were placed in pure water at a mass ratio of 9:1 for ultrasonic treatment for 0.8h, and product B was obtained after centrifugation and drying. Then product B was placed in a reactor in a nitrogen atmosphere, and a redox reaction was carried out at a high temperature of 2200℃ for 0.5min to obtain product C. Product C was sintered at 1000℃ in an oxygen-nitrogen mixed atmosphere with an oxygen content of 55%, and kept warm for 2h to obtain product D. Product D was reacted with 2.2mol / L sodium hydroxide solution to obtain nano β-SiC negative electrode material.

[0197] Comparative Example 3

[0198] The difference from Example 13 is that mixture A is polyamide, the temperature of the redox reaction is 800° C., and no product is finally produced.

[0199] Comparative Example 4

[0200] Different from Example 13, sucrose was used instead of the polymer, the temperature of the redox reaction was 550° C., and no product was finally produced.

[0201] Electrochemical performance test:

[0202] The silicon-based negative electrode material prepared in the above Examples 13 to 24 was used as the active material, copper foil was used as the current collector, the active material, Super P Li, and the binder were made into negative electrode sheets in a mass ratio of 8:1:1, and metallic lithium was used as the counter electrode to assemble a button-type half-cell.

[0203] The electrochemical performance test results are shown in Table 2.

[0204] Table 2 Electrochemical performance test results II

[0205]

[0206]

[0207] In Comparative Examples 3 and 4, since the carbon source does not contain halogen-substituted vinyl polymers, the redox reaction temperature is relatively low, β-SiC is not generated by the reaction, and no product is produced after sintering and etching.

[0208] Figure 7 This is the 100-cycle cycle curve of the battery prepared using the silicon carbide negative electrode material obtained in Example 13.

[0209] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a silicon carbide-coated silicon-based negative electrode material, characterized in that: include: The polymer and the silicon source are mixed and then subjected to a redox reaction to obtain a precursor; Sintering the precursor to obtain the silicon carbide-coated silicon-based negative electrode material; The temperature of the redox reaction is 1550-3000°C.

2. The method for preparing the silicon carbide-coated silicon-based negative electrode material according to claim 1, characterized in that: The polymer includes an M polymer, and the M polymer includes at least one of polyvinyl chloride, polytetrafluoroethylene, and polyvinylidene fluoride; Preferably, the polymer further comprises N polymers, and satisfies one or more of the following conditions: (1) The N polymer includes at least one of polyamide, polyacrylic acid, ethylene-vinyl acetate copolymer, polyethylene terephthalate, polybutylene terephthalate, polystyrene, and polycarbonate; (2) The mass ratio of the M polymer to the N polymer is (0.01-30.5):1; (3) The particle sizes of the M polymer and the N polymer are independently 0.05-500 μm.

3. The method for preparing the silicon carbide-coated silicon-based negative electrode material according to claim 1 or 2, characterized in that: One or more of the following conditions are met: A. The silicon source includes silicon powder; B. The particle size of the silicon source is 0.01-400 μm; C. The mass ratio of the silicon source to the polymer is (0.01-100): 1; D. The mixing includes one or more of ultrasound, mechanical stirring, and vibration ball milling; E. The mixing time is 0.1-36h; F. The mixed solvent includes one or more of ethanol, pure water, isopropanol, ether, methyl acetate, and acetone; G. The atmosphere of the redox reaction includes one or more of nitrogen, air, argon, carbon dioxide, and oxygen; H. The temperature of the redox reaction is 2000-3000°C, and the reaction time is 0.01-60min; I. The sintering atmosphere is a mixture of oxygen and nitrogen, a mixture of oxygen and argon, or a mixture of oxygen and carbon dioxide, wherein the volume content of oxygen is not less than 1%; J. The sintering temperature is 300-2000°C and the insulation time is 1-12h.

4. A silicon carbide-coated silicon-based negative electrode material, characterized in that: The method for preparing the silicon carbide-coated silicon-based negative electrode material according to any one of claims 1 to 3 is used to prepare the material.

5. The silicon carbide-coated silicon-based negative electrode material according to claim 4, characterized in that: One or more of the following conditions are met: A. The particle size of the silicon carbide coated silicon-based negative electrode material is 0.01-500 μm; B. The silicon carbide coated silicon-based negative electrode material comprises a core and a shell coating the core, the particle size of the core is greater than or equal to 0.01 μm and less than 500 μm, and the thickness of the shell is 0.0001-100 μm.

6. A method for preparing a silicon carbide negative electrode material, characterized in that: include: The silicon carbide-coated silicon-based negative electrode material according to claim 4 or 5 is etched with an etching solution.

7. The method for preparing the silicon carbide negative electrode material according to claim 6, characterized in that: The etching solution includes one or more of potassium hydroxide, sodium hydroxide, tetramethylammonium hydroxide, hydrochloric acid, hydrofluoric acid, and ethylenediaminocatechol; Preferably, the concentration of the etching solution is 0.1-5 mol / L.

8. A silicon carbide negative electrode material, characterized in that: The silicon carbide negative electrode material is prepared by the method for preparing the silicon carbide negative electrode material according to claim 6 or 7.

9. A secondary battery, characterized in that: The raw materials include the silicon carbide coated silicon-based negative electrode material described in claim 4 and / or the silicon carbide negative electrode material described in claim 8.

10. An electrical equipment, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Cited By

  • KRAS G12D modulating compounds

    US12448400B2